2018
DOI: 10.1007/s10995-018-2613-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Knowledge and Unsafe Baby Sleep Position: A Cross-Sectional Survey in Southern Brazil

Abstract: Objective to evaluate women's knowledge about the best baby sleeping position and to identify factors associated with a greater probability of putting infants to sleep in an unsafe position, in Rio Grande, Southern Brazil. Method This is a cross-sectional population-based study that included all women who bore children in 2013 in this municipality. A single, standardized questionnaire was given within 48 h after delivery in the only two local maternity hospitals. The outcome was that women reported the lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
9
1
2
Order By: Relevance
“…However, a study conducted in another city in southern Brazil (Rio Grande) that investigated mothers’ intention to place infant in supine sleep position found that, in 2010, only 20% of mothers had this intention [21]. Another study conducted in the city of Rio Grande, but investigating maternal knowledge of infant sleep position found that, in 2013, 80.5% of mothers believed the best infant sleep position was sidelying [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted in another city in southern Brazil (Rio Grande) that investigated mothers’ intention to place infant in supine sleep position found that, in 2010, only 20% of mothers had this intention [21]. Another study conducted in the city of Rio Grande, but investigating maternal knowledge of infant sleep position found that, in 2013, 80.5% of mothers believed the best infant sleep position was sidelying [22].…”
Section: Discussionmentioning
confidence: 99%
“…Only one-third of the mothers preferred the supine sleeping position for their babies, and the lateral position was the most preferred. Studies conducted in different countries revealed that the ventral/ lateral position was preferred by 82.1% of the participants in Brazil, while the supine position/ lying on their back was preferred by 72.4% in The Netherlands, and 89% in Georgia [7,31,32]. Similar to these findings, 77.3% of the mothers preferred the supine sleep position in Colson et al's study [33].…”
Section: Safe and Unsafe Practices Performed By Mothersmentioning
confidence: 67%
“…Outro fator importante é esclarecer para a família a respeito do posicionamento adequado no momento do sono do recém-nascido. Nessa perspectiva, os profissionais de saúde têm o dever de orientar esses pais e familiares para o posicionamento de modo correto do RN, mantendo-o em decúbito lateral ou decúbito dorsal (Cesar et al, 2019).…”
Section: Discussionunclassified